2,4-Di-tert-butyl-6-[1-(3,5-di-tert-butyl-2-hydroxyphenyl)ethyl]phenyl 4-methylbenzenesulfonate - Wu, Jincai (International Union of Crystallography, 2008)
The title compound, C(37)H(52)O(4)S, was obtained by the reaction of 6,6′-(ethane-1,1-diyl)bis(2,4-di-tert-butylphenol) and 4-methylbenzene-1-sulfonyl chloride. The molecular conformation is stabilized by an intramolecular O—H⋯O hydrogen bond. Two of the tert-butyl groups are disordered over two sets of sites with occupancies 0.530 (15)/0.470 (15) and 0.615 (11)/0.385 (11).